Learning to use an invisible visual signal for perception - Di Luca, Massimiliano (2010)
How does the brain construct a percept of the world from sensory signals? One approach to this fundamental question is to investigate perceptual learning as induced by exposure to different statistical regularities in sensory signals [1–7]. For example, recent studies showed that exposure to novel correlations between different sensory signals can cause a signal to have new perceptual effects [2,3]. In all those studies, however, the signals were always clearly visible. The automaticity of the learning was therefore difficult to determine. Here, we investigate whether learning of this sort, that causes a signal to have new effects on appearance, can be low-level and automatic, by employing a visual signal whose perceptual consequences were made invisible—a vertical disparity gradient masked by other depth cues. This approach excluded high-level influences such as attention or consciousness. Our stimulus for probing perceptual appearance was a rotating cylinder. During exposure we introduced a new contingency between the invisible signal and the rotation direction of the cylinder. When we subsequently presented an ambiguously rotating version of the cylinder, we found that the invisible signal influenced the perceived rotation direction. This demonstrates that perception can rapidly undergo “structure learning” by automatically picking up novel contingencies between sensory signals, thus automatically recruiting signals for novel uses during the construction of a percept.